Differential Mental Health Impact Six Months After Extensive River Flooding in Rural Australia: A Cross-Sectional Analysis Through an Equity Lens - Matthews, Veronica; Longman, Jo; Berry, Helen L.; Passey, Megan; Bennett-Levy, James; Morgan, Geoffrey G.; Pit, Sabrina; Rolfe, Margaret; Bailie, Ross S. (Frontiers in Public Health, 2019)
Background: Northern New South Wales in Australia is a 'hotspot' for natural disaster declarations with recent extensive flooding in early 2017. With limited knowledge about how climate change affects mental health and resilience, robust local assessments are required to better understand long-term impact, particularly in communities prone to extreme weather events. Methods: Six months post-flood, a cross-sectional survey of adults living in the region during the flood was conducted to quantify associations between flood impact and psychological morbidity (post-traumatic stress (PTSD), anxiety, depression, suicidal ideation) for different exposure scenarios and respondent groups. We adopted a community-academic partnership approach and purposive recruitment to increase participation from marginalised groups. Results: Of 2,180 respondents, almost all (91%) were affected by some degree of flood-related exposure at an individual and community level (ranging from suburb damage to home or business inundated). Socio-economically marginalised respondents were more likely to have their homes inundated and to be displaced. Mental health risk was significantly elevated for respondents: whose home/business/farm was inundated (e.g., home inundation: PTSD adjusted odds ratio (AOR) 13.72 (99% CI 4.53-41.56)); who reported multiple exposures (e.g., three exposures: PTSD AOR 6.43 (99% CI 2.11-19.60)); and who were still displaced after six months (e.g., PTSD AOR 24.43 (99%CI 7.05-84.69)). Conclusion: The 2017 flood had profound impact, particularly for respondents still displaced and for socio-economically marginalised groups. Our community-academic partnership approach builds community cohesion, informs targeted mental health disaster preparedness and response policies for different sectors of the community and longer-term interventions aimed at improving community adaptability to climate change.